ANALYSIS OF COMMUNITY PARTICIPATION IN 3R-BASED WASTE MANAGEMENT IN LHOKNGA SUBDISTRICT, ACEH BESAR REGENCY - Ananda, Raisa Dea; Fathma, Syarifah Seicha (Indonesian Journal of Environmental Sustainability, 2026)
Waste management in Lhoknga Subdistrict, Aceh Besar Regency, continues to pose a significant environmental challenge requiring urgent attention. This study aims to analyze the level of community participation in 3R-based (Reduce, Reuse, Recycle) waste management and to examine the relationship between individual characteristics and participation levels. The study employed a quantitative approach using questionnaires distributed to 100 randomly selected respondents. The collected data were analyzed using descriptive and inferential statistical methods through Partial Least Squares Structural Equation Modeling (PLS-SEM) implemented in SmartPLS 4.0. The results indicated that the highest level of community participation occurred in labor contributions (70%), followed by material contribution (53%), waste management practices (51%), and ideas (47%), whereas skills-based participation was the lowest (37%). The SmartPLS analysis revealed that individual characteristics significantly influenced participation in ideas (P=0.000), labor (P=0.002), and skills (P=0.012), but had no significant effect on material contribution (P=0.230) and waste management practices (P=0.242). These findings indicate that enhancing community participation in 3R-based waste management requires educational and community empowerment programs tailored to local community characteristics, supported by adequate waste management infrastructure and sustained government commitment.